Phenomenology Subjektif Well Being dan Kearifan Lokal pada Budaya Batak Suku Batak Toba Studi: Hamoraon, Hagabeon, Hasangapon - Sondang T. Silaban; Anggi Muthia Dewi; Ridna Shafira; Tania Salsabila; Tengku Havidz Syahputra (LPPM Institut Pendidikan Nusantara Global, 2026)
This study explores the meaning of Subjective Well-Being (SWB) within the cultural context of the Batak Toba community, grounded in the values of Hamoraon (wealth), Hagabeon (descendants), and Hasangapon (honor). Using a qualitative phenomenological approach, the research examines the lived experiences of two middle-aged Batak Toba women who had been married for over fifteen years without male offspring. Data were collected through in-depth interviews, participant observation, and documentation, and analyzed using phenomenological stages including epoche, horizonalization, meaning clustering, and the development of textural and structural descriptions. Findings reveal that SWB in Batak Toba culture is not solely determined by personal satisfaction but strongly shaped by social recognition and adherence to collective cultural values. The absence of a male child is perceived as failure to fulfill Hagabeon, leading to anxiety, shame (maila), feelings of inadequacy, and withdrawal from customary social activities. Although both participants were economically stable, material sufficiency (Hamoraon) alone was insufficient to ensure well-being without lineage continuity and social honor. However, acceptance of destiny, spirituality, and kinship support within the Dalihan Na Tolu system functioned as sources of psychological resilience. The study critically highlights the limitations of material-centered definitions of well-being and emphasizes that, in this cultural context, relational and lineage-based recognition plays a central role in shaping subjective well-being.